Optimizing Organizational Performance through Strategic Human Capital Management - Firdaus, Moh; Rosita, Wita; Diyanto, Hendi; Supratikta, Hadi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
The pivotal role of human capital in organizational success is increasingly recognized in contemporary business environments. This study presents an in-depth analysis of how strategic human capital management can significantly enhance company performance. Utilizing a qualitative approach, grounded in a comprehensive literature review, our research explores various strategies that can be employed to improve human resource performance in organizations. We emphasize that the success of a company hinges not just on its business operations, but critically on its human capital – the unique knowledge and skills possessed by its workforce. This research argues that the nuances of human capital, such as education, skills, and health, are essential for the strategic development of an organization. By implementing effective human capital strategies, companies can foster an environment conducive to growth, innovation, and long-term sustainability. Our findings highlight that understanding and leveraging the unique attributes of human resources can lead to significant improvements in organizational activities and outcomes. This paper contributes to the ongoing discourse on human capital theory by demonstrating its practical application in organizational strategy and performance enhancement.